Current Collectors: A Printable Metallic Current Collector for All‐Printed High‐Voltage Micro‐Supercapacitors: Instantaneous Surface Passivation by Flash‐Light‐Sintering Reaction (Adv. Funct. Mater. 25/2020). (18th June 2020) - Chae, Changju; Han, Jae Hee; Lee, Sun Sook; Choi, Youngmin; Kim, Tae‐Ho; Jeong, Sunho
Abstract : In article number 2000715, Youngmin Choi, Tae‐Ho Kim, Sunho Jeong, and co‐workers propose a printable metallic current collector for all‐printed, solid‐state micro‐supercapacitors, developed by using a multi‐dimensional printable particle mixture and flash‐light sintering technique. It is revealed that the resulting metallic current collector is stable at a voltage condition as high as 3 V in carbon electrode‐based devices, enabling an areal energy density of 79–23 mJ cm −2 at an areal power density of 0.4–12.8 mW cm −2 .